Rapid evolution of fluoroquinolone-resistant Escherichia coli in Nigeria is temporally associated with fluoroquinolone use - Lamikanra Adebayo (BMC Infectious Diseases, 2011)
Abstract Background Antibiotic resistance has necessitated fluoroquinolone use but little is known about the selective forces and resistance trajectory in malaria-endemic settings, where selection from the antimalarial chloroquine for fluoroquinolone-resistant bacteria has been proposed. Methods Antimicrobial resistance was studied in fecal Escherichia coli isolates in a Nigerian community. Quinolone-resistance determining regions of gyrA and parC were sequenced in nalidixic acid resistant strains and horizontally-transmitted quinolone-resistance genes were sought by PCR. Antimicrobial prescription practices were compared with antimicrobial resistance rates over a period spanning three decades. Results Before 2005, quinolone resistance was limited to low-level nalixidic acid resistance in fewer than 4% of E. coli isolates. In 2005, the proportion of isolates demonstrating low-level quinolone resistance due to elevated efflux increased and high-level quinolone resistance and resistance to the fluoroquinolones appeared. Fluoroquinolone resistance was attributable to single nucleotide polymorphisms in quinolone target genes gyrA and/or parC. By 2009, 35 (34.5%) of isolates were quinolone non-susceptible with nine carrying gyrA and parC SNPs and six bearing identical qnrS1 alleles. The antimalarial chloroquine was heavily used throughout the entire period but E. coli with quinolone-specific resistance mechanisms were only detected in the final half decade, immediately following the introduction of the fluoroquinolone antibacterial ciprofloxacin. Conclusions Fluoroquinolones, and not chloroquine, appear to be the selective force for fluoroquinolone-resistant fecal E. coli in this setting. Rapid evolution to resistance following fluoroquinolone introduction points the need to implement resistant containment strategies when new antibacterials are introduced into resource-poor settings with high infectious disease burdens.